(untitled) (International Journal of Environmental Sciences, 2025)
Diabetes mellitus is considered as a metabolic disorder characterized by high level of glucose in blood stream. Diabetes is associated with impaired carbohydrate, fat and protein metabolism resulting from either the deficiency of insulin secretion or decreased sensitivity of cells to recognize insulin action that leads to insulin resistance. In the diabetic environment low density lipoprotein (LDL) are typically exposed to high level of circulating glucose and in result glycated LDL are formed. Similarly, some LDL molecules are modified by reactive oxygen species (ROS) and become oxidized low-density lipoprotein (Ox-LDL) particles. This study was done to determine the association between dietary intake and Ox-LDL. Physical, clinical and biomedical assessment was done by using food frequency questionnaire and taking blood samples. The concentration of Ox-LDL was determined by using human Ox-LDL Elisa kit. Pearson correlation and regression analysis were used to determine the correlation between Ox-LDL concentration and body mass index (BMI), calories intake, fruit intake, blood glucose, carbohydrate (CHO) intake, processed foods, fat intake and no. of servings. Study has found that Ox-LDL levels increased in diabetic patients. Ox-LDL is positively correlate with BMI, calories, blood glucose, and no. of servings, fat intake, processed foods and CHO intake. Thus, Ox-LDL can be reduced by low CHO, good fat and fruit intake.